New Insights About the Behavioral Ecology of the Coelacanth Latimeria chalumnae Video Recorded in the Absence of Humans Off South Africa - Jiro Sakaue (Frontiers Media S.A., 2021)
South African coelacanths, Latimeria chalumnae, were intensively studied using submersibles in the Comoros Islands before recent progress in deep-diving techniques led to the discovery of coelacanths living at shallower depths off Sodwana Bay, South Africa, which were then studied by divers in close encounters or from underwater vehicles. However, all previous observations were made under intense human influence, so the “natural” behaviors of coelacanths have never been observed. Here we sought to record the natural behaviors of coelacanths by minimizing anthropogenic influences using trimix-gas diving and remote recording techniques. We thus set fixed camera and current/temperature recorders at 98 and 113 m to monitor the behaviors of fishes and oceanographic parameters over a 6-day period. Time-lapse video observations succeeded to record one coelacanth that entered the cave during the coldest-water period, two sand tiger sharks, and many other smaller fishes entering a cave. An extensive analysis of the footage led to an interesting discovery that the first dorsal fin angle of the coelacanth corelated with the presence-or-absence of a large shark that frequently passed through the cave. When no shark was present, the coelacanth’s dorsal fin was folded ∼3/4 of the time, but when the shark entered the cave, its dorsal fin was unfolded > 95% of the time, while no such reactions were observed with other observed fishes. The erected coelacanth first dorsal fin posture is an important part of the iconic symbol of these ancient fish, but it may be reflecting stressful situations such as responses to potential predators. Our observation clearly showed that the dorsal fin is in a folded position during a steady relaxed state of the fish and it can be unfolded in response to external stimuli. Use of non-biased observation systems is strongly recommended when observing the natural behavior of coelacanths.